PARE0017 Recommendations for Rheumatologists on Physical Exercise in Spondyloarthritis (EJES 3-D Study). (9th June 2015) - Loza, J.; Carmona, L.; Zarco, P.; Flόrez, M.T.
Abstract : Background: Despite the growing body of evidence to support the importance of exercise in the management of ankylosing spondylitis (AS), fewer than one-quarter of patients with AS exercise frequently. Several factors could explain it, including the lack of related specific knowledge among many rheumatologists or patient's barriers to exercise. Therefore, we need a broad and multidisciplinary approach in order to design an effective strategy to prescribe and monitor physical exercise in SpA patients. Objectives: 1) To establish recommendations on exercise for SpA patients; 2) to provide motivational actions and facilitators for an active exercise prescription by rheumatologists; 3) to provide motivational actions and facilitators to improve patients adherence to exercise. Methods: A guided discussion group of rheumatologists with expertise on SpA was organized on issues the rheumatologists considered important when indicating and evaluating the effect of physical exercise in SpA patients, as well as on their current knowledge on this field and potential gaps or needs. The results of a systematic literature review about factors that improve adherence to exercise, the results of two discussion groups of patients (to explore barriers and facilitators to exercise), and the results of a focus group of exercise specialists (to define effective exercises for SpA patients and how messages should be given in order to be more effective) were presented and discussed. Results: The following consensus recommendations were drawn out: How to prescribe. SpA patients should be prescribed aerobic exercise of moderate intensity the same as general population and exercise programs similar to the American College of Sports Medicine recommendations, adapted to patients and disease characteristics. Although there is little limitation evidence to support it, it is important to do some type of aerobic exercise at all disease stages. Besides, in cases of ankylosis, forced stretching can be dangerous and are unuseful. Exercises in painful areas should be avoided in phases of activity and postural education must be provided. How to motivate rheumatologists. The following points were proposed: To agree on physical exercise with exercise specialists, to increase knowledge about the evidence based benefits of exercise in SpA and training on exercise. Including all these recommendations in a specifically designed website with a frequently asked questions section, explaining basics of exercise, and examples of the exercises they are prescribing might also help. How to motivate patients: The following points were agreed: to spend more time in daily practice for exercise issues, to provide positive and personalized messages without mentioning directly neither the structural damage of the disease nor depressing information, but being realistic, to explain properly the exercises the patient must not do. It was also argued that patients' associations can be effective promoters. Conclusions: Rheumatologists believe that they require more knowledge about exercise in order to prescribe it appropriately. With all this information an specific tool for prescribing exercise in SpA is being developed, as well as an implementation strategy that should facilitate adherence and patient self-management for both the start and the maintenance of the exercise program. Acknowledgements: Funded by an unrestricted grant from Merck Sharp & Dohme (Spain). Disclosure of Interest: None declared